Micronutrient Deficiencies in the Palestinian Territories : Identifying the Bottlenecks of Anemia Prevention and Control and Assessing the Feasibility of an Oil Fortification Program - Hasumi, Takahiro (World Bank, Washington, DC, 2022)
In the Palestinian territories (PT), decades of conflict, economic stagnation, and restricted movement of people and goods, coupled with high unemployment and poverty rates, continue to affect social, health, and nutrition indicators. For decades, several assessments have indicated a poor nutritional status of the population in the West Bank (WB) and Gaza Strip (GS). Specifically, a high prevalence of micronutrient deficiencies still exists among pregnant and postnatal women and children of ages 6–23 months despite multiple initiatives to address them. Micronutrient deficiencies are one form of undernutrition that occur because of insufficient intake or sufficient intake coupled with inadequate absorption due to infection, disease, or inflammation. Two detailed assessments were conducted (1) to identify the bottlenecks of anemia prevention and control programs in the PT and (2) to examine the feasibility of an edible oil fortification program. Due to the COVID-19 outbreak and conflicts, the assessments largely relied on the use of readily available data for secondary analyses and remote data collection through online/phone surveys, key informant interviews, and focus group discussions. To the extent possible, the assessments collected data from key informants (for example, health care service providers) and beneficiaries through field visits and stakeholder interviews. The detailed methodology for each of the assessments areavailable in annexes 1 and 2.